Understanding diverse approaches to predator management among gamekeepers in England. Issue 2 (3rd May 2020) - Swan, George J. F.; Redpath, Steve M.; Crowley, Sarah L.; McDonald, Robbie A.
Abstract: Disagreements and disputes over the management of predatory animals are a frequent feature of conservation conflicts. In the UK, there are long‐standing conflicts surrounding legal and illegal killing of predators as part of management fostering game species as quarry for sport shooting. Despite the central role of gamekeepers as stakeholders and actors in this predominant form of predator management, little direct attention has been paid to their perspectives and motivations. We conducted semi‐structured interviews on the subject of predator management with 20 gamekeepers across the south of England and applied a social‐psychological approach to explore the underlying beliefs, norms and information sources associated with their actions. Data were analysed for patterns in terminology, rationalization or subject and synthesized into broad 'motivations', which were structured using a framework from the Theory of Planned Behaviour (TPB). Six primary motivations for predator management emerged: professional identity, personal norms, potential penalties, perceived impact, personal enjoyment and perceived ease. Perceived impact of predators on released game, and wildlife more broadly, was a central driver of predator killing. We identified three indirect influences on how this impact is judged: 'maintaining balance', 'appeal to nature' and 'problem individuals'. We find that predator killing by gamekeepers is not solely a function of perceived economic loss but a product of multiple factors, including perceived professional norms, a sense of personal responsibility for game and non‐game wildlife, and assessments of predator populations and behaviours based on personal encounters. Motivations were well characterized within the TPB framework, with links to subjective norms, attitudes and perceived behavioural control. Our use of this social‐psychological approach to understanding the actions and preferences of these key stakeholders highlights how behaviours that are central to conservation conflicts have multiple social and ecological drivers. Characterizing the multiple motivations behind predator killing might help address aspects of the social conflicts with which sport shooting is currently associated, if actions, deliberation and, where appropriate, mediation, can be targeted at the key concerns of these central stakeholders and actors. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.